Studying CO₂ conversion in DC glow discharge - Lisovskiy, V.A.; Dudin, S.V.; Platonov, P.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2020)
We have registered the mass-spectra of the gas mixture leaving the chamber and the discharge current-voltage characteristics and determined the specific energy input (SEI), the absolute conversion coefficient χ and the conversion energy efficiency η in the CO₂ pressure range of 0.05…5 Torr. Converting CO₂ molecules was performed in the glow discharge in a chamber with distributed same-side gas supply and pumping. As a result the conversion coefficient χ equaling 70% was achieved, but the conversion energy efficiency η did not exceed 1…3% because of considerable power loss due to acceleration of positive ions, gas and electrode heating as well as to inelastic collisions between electrons and gas molecules not leading to CO₂ conversion. За допомогою виміряних мас-спектрів газової суміші, що виходить з камери, а також вольт-амперних характеристик розряду визначені питомий енергетичний внесок (SEI), абсолютний коефіцієнт конверсії χ та енергетична ефективність конверсії η в діапазоні тиску CO₂ 0,05…5 Торр. Процес плазмової конверсії молекул CO₂ проводився у тліючому розряді в камері з розподіленими напусканням та відкачуванням газу з одного боку. У результаті досягнута величина коефіцієнта конверсії χ~70%, проте енергетична ефективність конверсії η не перевищувала 1…3% через значні втрати потужності на прискорення позитивних іонів, нагрівання електродів і газу, а також при непружних зіткненнях електронів з молекулами газу, які не призводять до конверсії CO₂. С помощью измеренных масс-спектров газовой смеси, выходящей из камеры, а также вольт-амперных характеристик разряда определены удельный энергетический вклад (SEI), абсолютный коэффициент конверсии χ и энергетическая эффективность конверсии η в диапазоне давлений CO₂ 0,05…5 Торр. Процесс плазменной конверсии молекул CO₂ проводился в тлеющем разряде в камере с распределенными напуском и откачкой газа с одной стороны. В результате достигнута величина коэффициента конверсии χ~70%, однако энергетическая эффективность конверсии η не превышала 1…3% из-за значительных потерь мощности на ускорение положительных ионов, нагрев электродов и газа, а также при неупругих столкновениях электронов с молекулами газа, которые не приводят к конверсии CO₂.